Effect of Composition and Impurities on the Phosphorescence of Green-Emitting Alkaline Earth Aluminate Phosphor - Kim, Doory (PLoS One, 2016)
Recent improvements to SrAl(2)O(4):Eu(2+), Dy(3+) phosphors have enabled the use of luminescent hosts with a stable crystal structure and high physical and chemical stability, thus overcoming the bottleneck in the applicability of ZnS:Cu phosphors. However, enhancement of afterglow lifetime and brightness in SrAl(2)O(4):Eu(2+), Dy(3+) phosphors remains a challenging task. Here, we have improved the afterglow characteristics in terms of persistence time and brightness by a systematic investigation of the composition of Eu-doped alkaline earth aluminate SrAl(2)O(4):Eu(2+), Dy(3+) crystals. We found that a Dy(3+)/Eu(2+) ratio of ~2.4 and ~0.935 mol Eu(2+) (per mol of SrAl(2)O(4)) gave the brightest and longest emissions (11% and 9% increase for each). Doping with Si(4+) also resulted in a slight increase in brightness up to ~15%. Doping with alkali metal or alkaline earth metal significantly enhanced the phosphorescence intensity. In particular, doping with 0.005 mol Li(+) (per mol of SrAl(2)O(4)) alone boosted the phosphorescence intensity to 239% of the initial value, as compared to that observed for the non-doped crystal, while doping with 0.01 mol Mg(2+) and 0.005 mol Li(+) (per 1 mol SrAl(2)O(4)) boosted the phosphorescence intensity up to 313% of the initial value. The results of this investigation are expected to act as a guideline for the synthesis of bright and long persistent phosphors, and facilitate the development of persistent phosphors with afterglow characteristics superior to those of conventional phosphors.